Voice and data communications handbook - Bates, Regis J.; Gregory, Donald W. (New York : McGraw-Hill, 2001)
Engineering
2002-06-04
Keywords: Data communication-Handbook; Voice communication-Handbook; Telecommunication-History; Analog communication; Digital communication; Voice processing; Internet; Intranet; LAN